2022
DOI: 10.1016/j.pmedr.2021.101688
|View full text |Cite
|
Sign up to set email alerts
|

Marketing of sugar-sweetened beverages to youth through U.S. university pouring rights contracts

Abstract: Highlights Coca-Cola, Pepsi, and Gatorade partner with universities to market beverages. 16% of university beverage contracts targeted marketing at youth under 18 years old. Nearly all youth-targeted beverage marketing was tied to university athletics. Contracts noted that they may be affected by laws limiting advertising to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…The sweetener HFCS is a health concern problem because it is associated with NAFLD with and without metabolic symptoms ( 93 ). The higher consumers of SSBs are youths (especially of color) influenced by attractive marketing ( 12 , 94 ). On the other hand, new ways to deliver Nic have been introduced in the market as electronic cigarettes that lead to hepatic steatosis ( 34 ), and are extremely popular among youth, with attractive marketing offering different technological formats and flavors, such as vanilla are by themselves toxic for hepatic cells after in vitro exposure ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sweetener HFCS is a health concern problem because it is associated with NAFLD with and without metabolic symptoms ( 93 ). The higher consumers of SSBs are youths (especially of color) influenced by attractive marketing ( 12 , 94 ). On the other hand, new ways to deliver Nic have been introduced in the market as electronic cigarettes that lead to hepatic steatosis ( 34 ), and are extremely popular among youth, with attractive marketing offering different technological formats and flavors, such as vanilla are by themselves toxic for hepatic cells after in vitro exposure ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional details about our study are reported elsewhere. ( Nestle, 2001 , Marx et al, 2021 , Zaltz et al, 2022 ) Briefly, we limited our sample to 4-year degree granting public universities, as determined by the National Center for Education Statistics’ Integrated Postsecondary Education Data System. To be included, universities had to be based in the US, have 20,000 students enrolled, and have contracts that were active at any point from 2018 to 2019.…”
Section: Methodsmentioning
confidence: 99%
“… 6 PRCs incentivize schools to market SSBs and maximize sales through volume incentives and volume minimums, and contract stipulations can even interfere with water availability. 7 , 8 , 9 , 10 The promotion and marketing of SSBs in higher education directly conflicts with recommendations from major public health organizations (e.g., Centers for Disease Control and Prevention, American Heart Association, and National Academy of Medicine) that institutions reduce SSB availability, marketing, and consumption. 11 , 12 , 13…”
Section: Introductionmentioning
confidence: 99%